Liver involvement in pediatric Hodgkin lymphoma: A systematic review by an international collaboration on Staging Evaluation and Response Criteria Harmonization (SEARCH) for Children, Adolescent, and Young Adult Hodgkin Lymphoma (CAYAHL). Issue 8 (3rd June 2020) - Hagleitner, Melanie M.; Metzger, Monika L.; Flerlage, Jamie E.; Kelly, Kara M.; Voss, Stephan D.; Kluge, Regine; Kurch, Lars; Cho, Steve; Mauz‐Koerholz, Christine; Beishuizen, Auke
Abstract: Hepatic involvement in Hodgkin lymphoma (HL) is uncommon (∼5% of patients) but always implies stage IV disease. Accurate staging is mandatory for making the appropriate risk assignment and treatment decisions. The Staging Evaluation and Response Criteria Harmonization for Childhood, Adolescent and Young Adult Hodgkin Lymphoma (SEARCH for CAYAHL) international working group conducted a systematic literature review of liver involvement in HL patients with the aim to propose a universally acceptable definition for liver involvement in pediatric HL. Thirty‐three articles describing 6985 pediatric and adult HL patients were reviewed, of which 539 (7.7%) mentioned liver involvement. The literature did not provide a uniform definition of hepatic involvement and we propose consensus criteria derived from the EuroNet and Children's Oncology Group protocols, where liver involvement is defined as any hepatic lesion on computed tomography scan that correlates with 18 F‐FDG uptake greater than background liver. A clear definition of liver lesions is necessary to consistently identify liver involvement and compare its impact on outcomes among protocols worldwide.